Presence and site-matching of ischemia at stress-scintigraphy or contrast stress-echo in individuals developing myocardial infarction within 3 months: does stenosis severity matter? - Siniscalchi, Carmine; Reverberi, Claudio; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2016)
Background and aim: Individuals with ischemia during cardiac stress-test (cST) have a high risk of developing myocardial infarction (MI), but the pathophysiologic mechanism has never been clarified. It is thought that non flow-limiting coronary plaques (FLP) cause more often MI than FLP, but this is in contradiction with the predictive value of cST. We investigated the correspondence between reversible ischemia and location of subsequent MI, since functional assessment shortly before MI could clarify whether the culprit plaque is a FLP or not. Methods: From 4505 MI and 4959 cST -2017 contrast perfusion stress-echo (cDipSE) and 2942 scintigraphy (SPECT)- performed from 2007 to 2011- 25 patients fulfilling criteria (<3 months between cST and subsequent MI, angiography within 72 hours of symptoms onset and no revascularization between cST and MI) were extracted and data matched. Reversible perfusion defects were considered the endpoint to define a positive cST. Results: Reversible perfusion defects on cST were found in 84% of patients (21/25) and 80% (20/25) had matched defects; 95% (20/21) of patients demonstrating a reversible defect had a subsequent MI in the same territory. Conclusion: Our data suggest that when cST-MI time is shortened, and plaque progression bias consequently minimized, most MI (80%) develop in the coronary territory where reversible perfusion defects were detected shortly before. These data encourage reconsidering FLP as main determinant of MI.